Follow the process of completing the square to solve x2 = -4x + 3.

Which of the following equations is used in this process?

A. (2x + 4)2 = 12
B. (2x + 4)2 = 19
C. (2x + 4)2 = 28

Respuesta :

Answer:

(2x+4)^2 = 28

Step-by-step explanation:

[tex]x^2 = -4x + 3[/tex]

to apply completing the square method we need x terms on one side

add 4x on both sides

[tex]x^2+4x = 3[/tex]

Now we take the coefficient of x  term and divide by 2

4 divide by 2 is 2

Now we square it (2)^2 = 4

In completing the square method, we add that number on both sides

[tex]x^2+4x+4 = 3+ 4[/tex]

Now we factor x^2 + 4x + 4

(x+2)(x+2) = 7

(x+2)^2 = 7

(x+2)(x+2) = 7

Multiply both sides by 4

2(x+2) * 2(x+2) = 7* 4

(2x+4)(2x+4) = 28

(2x+4)^2 = 28